A composite positive electrode material and preparation method thereof and lithium ion battery

By using a composite positive electrode material coated with solid electrolyte in lithium cobalt oxide in lithium-ion batteries, the capacity attenuation problem caused by side reactions in the battery is solved, and higher cycle stability and energy density are achieved.

CN117543021BActive Publication Date: 2025-01-07SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410034622.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-10
Publication Date
2025-01-07
Estimated Expiration
2044-01-10

AI Technical Summary

Technical Problem

The side reaction between the positive electrode material and the electrolyte at the interface in lithium-ion batteries causes the capacity of lithium ions to decay, affecting the cycling stability and energy density of the battery.

Method used

The preparation method of composite positive electrode material is adopted, and a solid electrolyte is used to coat lithium cobalt oxide through mechanical dispersion and one-step sintering method to block the contact between the electrolyte and lithium cobalt oxide and reduce side reactions.

Benefits of technology

It significantly improves the cycle stability and capacity retention rate of lithium-ion batteries and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117543021B_ABST
    Figure CN117543021B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium-ion batteries, and discloses a method for preparing a composite positive electrode material, comprising the steps of: providing a solid electrolyte, lithium cobalt oxide and a solvent; mixing the solid electrolyte with the solvent and grinding until the solvent evaporates to obtain a mixture; adding the lithium cobalt oxide and the solvent to the mixture and grinding until the solvent evaporates to obtain a composite positive electrode material precursor; sintering the composite positive electrode material precursor to obtain a composite positive electrode material, wherein the composite positive electrode material comprises a core layer and a shell layer, wherein the material of the core layer is the lithium cobalt oxide, and the material of the shell layer is the solid electrolyte. The present application prepares the composite positive electrode material by combining mechanical dispersion with one-step sintering, and the preparation method is simple and easily applicable to industrial production. When the composite positive electrode material prepared by the preparation method of the present application is used for the positive electrode of a battery, the capacity retention rate of the battery does not decay or decays very little, and has extremely excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a composite positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Since its commercialization in 1991, lithium-ion batteries (LIBs) have conquered the main energy storage market of portable electronics and electric vehicles (EVs) with their high energy density / efficiency and long cycle life. Currently, with the continuous development of modern society, higher requirements are placed on the energy density of LIBs. In particular, the progress of 3C (computer, communication and consumer) electronic products that provide more energy on the basis of being smarter and more portable has focused more on the high volumetric energy density of lithium-ion batteries. Since LiCoO2 was applied by Goodenough in 1980, it has been widely used in the energy storage field due to its high energy density, high voltage platform (3.7-3.9V), high loading capacity (4.1-4.3 g / cm 3 ) and easy processing advantages, it occupies a dominant position in the 3C electronics field.

[0003] Lithium-ion batteries with lithium cobalt oxide (LiCoO2) cathodes are widely charged to a cutoff voltage of 4.2 V to maintain structural stability, in which only half a mole of Li ions are extracted from the lithium layer, providing only about 140 mAh / g of reversible capacity, which is only half of its theoretical capacity (274 mAh / g), far from the requirements of high energy density. With the repeated insertion and extraction of lithium ions, LiCoO2 undergoes volume changes, resulting in increased impedance and poor cycle performance. Therefore, in the portable electronics market, further improving the long-cycle stability of LiCoO2 cathode batteries is crucial to effectively meet demand and bring huge commercial benefits. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a composite positive electrode material and a preparation method thereof and a lithium-ion battery, aiming to solve the problem that the positive electrode material is prone to side reactions at the interface with the electrolyte of the lithium-ion battery, thereby causing the capacity of lithium ions to decay in long cycles.

[0005] The technical solution of this application is as follows:

[0006] In a first aspect of the present application, a method for preparing a composite positive electrode material is provided, comprising the steps of:

[0007] S1. Provide solid electrolyte, lithium cobalt oxide and solvent;

[0008] S2, mixing the solid electrolyte and the solvent and grinding until the solvent evaporates to obtain a mixture;

[0009] S3, adding the lithium cobalt oxide and the solvent to the mixture and grinding until the solvent evaporates to obtain a composite positive electrode material precursor;

[0010] S4, sintering the composite positive electrode material precursor to obtain a composite positive electrode material;

[0011] The composite positive electrode material comprises a core layer and a shell layer, the material of the core layer is lithium cobalt oxide, and the material of the shell layer is the solid electrolyte.

[0012] Optionally, the solid electrolyte includes Li 1+x Al x M 2-x (PO4)3, LiTiPO5; wherein M includes at least one of Ti, Ge, Sr, 0.2≤x≤0.5.

[0013] Optionally, the solvent includes at least one of water, anhydrous ethanol and N-methylpyrrolidone.

[0014] Optionally, the mass ratio of the solid electrolyte to the lithium cobalt oxide is 0.005-0.04:1.

[0015] Optionally, in S2, the mass ratio of the solvent to the solid electrolyte is 0.005~0.08:1.

[0016] Optionally, in S3, the mass ratio of the solvent to the lithium cobalt oxide is 1-2:1.

[0017] Optionally, the sintering temperature is 750-900° C., the sintering heating rate is 3-5° C. / min, and the sintering holding time is 4-6 h.

[0018] Optionally, the preparation method further comprises repeating S2 and S3 before S4, the number of repetitions being 3 to 5 times.

[0019] In a second aspect of the present application, a composite positive electrode material prepared by the above-mentioned composite positive electrode material preparation method is provided.

[0020] According to a third aspect of the present application, a lithium-ion battery is provided, wherein the lithium-ion battery comprises a positive electrode, and the positive electrode comprises the above-mentioned composite positive electrode material.

[0021] Compared with the prior art, this application has the following advantages:

[0022] The present application prepares a composite positive electrode material by combining mechanical dispersion with one-step sintering. The preparation method is simple and easy to apply to industrial production. The composite positive electrode material prepared by the preparation method of the present application includes a core layer containing lithium cobalt oxide and a shell layer containing a solid electrolyte. The shell layer containing the solid electrolyte completely covers the core layer containing lithium cobalt oxide. When used in lithium-ion batteries, the shell layer containing the solid electrolyte can block the contact between the electrolyte (or electrolyte) and the lithium cobalt oxide, effectively reducing the side reactions between the lithium cobalt oxide and the electrolyte (or electrolyte) in the composite positive electrode material at the interface, and solving the problem of rapid capacity decay of lithium-ion batteries caused by structural changes and / or side reactions during the cycle. As a result, the battery capacity retention rate does not decay or decays very little, and has extremely excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for describing the embodiments are briefly introduced below.

[0024] Figure 1 This is a capacity retention rate test chart provided in Example 1 of the present application;

[0025] Figure 2 This is a capacity retention rate test diagram provided in Example 2 of the present application;

[0026] Figure 3 This is a capacity retention rate test diagram provided in Example 3 of the present application;

[0027] Figure 4 This is a capacity retention rate test chart provided for comparative example 1 of the present application. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings and embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present application. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0029] It should be noted that if there are descriptions involving "first", "second", etc. in the implementation of this application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance and implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the fact that ordinary technicians in the field can implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0030] In a first aspect of an embodiment of the present application, a method for preparing a composite positive electrode material is provided, comprising the steps of:

[0031] S1. Provide solid electrolyte, lithium cobalt oxide and solvent;

[0032] S2, mixing the solid electrolyte with the solvent and grinding until the solvent evaporates to obtain a mixture;

[0033] S3, adding lithium cobalt oxide and a solvent to the mixture of S2 and grinding until the solvent evaporates to obtain a composite positive electrode material precursor;

[0034] S4. Sintering the composite positive electrode material precursor to obtain a composite positive electrode material.

[0035] By adding a certain amount of solvent to the solid electrolyte and a certain amount of solvent to the lithium cobalt oxide, the solid electrolyte and the lithium cobalt oxide can be better dispersed, and the composite positive electrode material is prepared by combining a one-step sintering method, and the positive electrode material is coated by a combination of a wet method and a dry method, and the coating effect is excellent. The operation is simple and easy to make, and it is suitable for industrial production. The solid electrolyte can completely coat the lithium cobalt oxide. When the composite positive electrode material is used to prepare the positive electrode of the battery, the solid electrolyte can block the contact between the lithium cobalt oxide in the composite positive electrode material and the electrolyte (or electrolyte) of the battery, effectively reducing the side reaction between the lithium cobalt oxide in the composite positive electrode material and the electrolyte (or electrolyte) at the interface, and solving the problem of rapid capacity decay of lithium-ion batteries caused by structural changes and / or side reactions during the cycle. In this way, the battery capacity retention rate does not decay or decays very little, and has extremely excellent cycle stability.

[0036] In one embodiment, S2 and S3 can be performed in a mortar or other equipment capable of grinding.

[0037] In one embodiment, the solid electrolyte comprises Li 1+x Al x M 2-x(PO4)3, LiTiPO5. M includes at least one of Ti, Ge, Sr, 0.2≤x≤0.5. Preferably, the solid electrolyte is Li 1.3 Al 0.3 Ti 1.7 (PO3)4、Li 1.4 Al 0.4 Ti 1.6 At least one of (PO3)4 and LiTiPO5.

[0038] In one embodiment, the lithium cobalt oxide includes at least one of high-rate lithium cobalt oxide, high-density lithium cobalt oxide, and high-voltage lithium cobalt oxide. Lithium cobalt oxide can be divided into high-temperature phase HT-LiCoO2, low-temperature phase LT-LiCoO2, and rock salt phase LiCoO2 according to the crystal structure. High-rate lithium cobalt oxide, high-density lithium cobalt oxide, and high-voltage lithium cobalt oxide are all high-temperature phase HT-LiCoO2.

[0039] In one embodiment, the solvent includes at least one of water, anhydrous ethanol, and N-methylpyrrolidone. For example, the solvent is water, anhydrous ethanol, N-methylpyrrolidone, a mixture of water and N-methylpyrrolidone, or a mixture of anhydrous ethanol and N-methylpyrrolidone.

[0040] In one embodiment, the mass ratio of the solid electrolyte to the lithium cobalt oxide is 0.005 to 0.04: 1. For example, the mass ratio of the solid electrolyte to the lithium cobalt oxide is 0.005: 1, 0.01: 1, 0.015: 1, 0.02: 1, 0.025: 1, 0.03: 1, 0.035: 1 or 0.04: 1, etc.

[0041] In one embodiment, in S2, the mass ratio of the solvent to the solid electrolyte is 0.005 to 0.08: 1. For example, the mass ratio of the solvent to the solid electrolyte is 0.005: 1, 0.01: 1, 0.02: 1, 0.04: 1, 0.06: 1 or 0.08: 1, etc.

[0042] In one embodiment, in S3, the mass ratio of the solvent to the lithium cobalt oxide is 1 to 2: 1. For example, the mass ratio of the solvent to the lithium cobalt oxide is 1: 1, 1.2: 1, 1.4: 1, 1.5: 1, 1.6: 1, 1.8: 1 or 2: 1.

[0043] By mixing the solid electrolyte and the solvent in proportion and grinding them until they are dry in a mortar (the solvent evaporates), and then adding lithium cobalt oxide and the solvent in proportion and grinding them until they are dry in a mortar (the solvent evaporates), friction, expansion, evaporation / drying and other processes occur in the mortar, so that the solid electrolyte and lithium cobalt oxide are better dispersed, which is conducive to the solid electrolyte coating on the positive electrode material. It can be understood that the amount of solvent added is very small, and it is easy to completely evaporate during the grinding process.

[0044] In one embodiment, in S2, the solvent and the solid electrolyte are mixed by dripping the solvent into the solid electrolyte; in S3, the solvent and the lithium cobalt oxide are mixed by dripping the solvent into the lithium cobalt oxide. Since the amount of solvent added is very small, the solvent and the solid electrolyte or the lithium cobalt oxide can be mixed more evenly by dripping. Preferably, the solvent and the solid electrolyte, and the solvent and the lithium cobalt oxide can be mixed by grinding and dripping, so that the mixing is more uniform, and the dispersion effect of the solid electrolyte and the lithium cobalt oxide is better. So that the solid electrolyte can be better coated on the lithium cobalt oxide.

[0045] In one embodiment, the sintering temperature may be 750-900°C. For example, the sintering temperature is 750°C, 800°C, 850°C or 900°C. The sintering heating rate may be 3-5°C / min. For example, the sintering heating rate is 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min. The sintering time may be 4-6h. For example, the sintering time is 4h, 4.5h, 5h, 5.5h or 6h.

[0046] By heating the composite cathode material precursor to 750-900°C at a heating rate of 3-5°C / min in a muffle furnace and other equipment, and keeping the temperature for 4-6 hours, the mechanical properties of the components of the composite cathode material precursor can be improved, and the composite cathode material can be better solidified. The sintering process can also be carried out in other equipment, which can be selected according to actual conditions.

[0047] In one embodiment, the method for preparing the composite positive electrode material of the embodiment of the present application comprises the steps of:

[0048] S1. Provide solid electrolyte, lithium cobalt oxide and solvent;

[0049] S2, adding a solid electrolyte to a mortar, dropping a solvent and grinding until dry in the mortar;

[0050] S3, adding lithium cobalt oxide to a mortar, adding dropwise solvent and grinding until dry in the mortar;

[0051] S4, repeat S2 and S3 three to five times to obtain a composite positive electrode material precursor;

[0052] S5. Sintering the composite positive electrode material precursor to obtain a composite positive electrode material.

[0053] By mixing and grinding the solid electrolyte and solvent in small amounts multiple times, and then adding lithium cobalt oxide and the solvent and mixing and grinding, the solid electrolyte and the positive electrode material can be mixed more evenly, so that the solid electrolyte can be better coated on the lithium cobalt oxide (positive electrode material).

[0054] According to a second aspect of an embodiment of the present application, a composite positive electrode material prepared by the above-mentioned composite positive electrode material preparation method is provided.

[0055] Among them, the composite positive electrode material includes a core layer and a shell layer, the core layer is lithium cobalt oxide, and the shell layer is a solid electrolyte. By using the solid electrolyte to coat the lithium cobalt oxide, when the composite positive electrode material is used in a lithium-ion battery, the solid electrolyte can block the contact between the lithium cobalt oxide and the electrolyte (or electrolyte) in the lithium-ion battery, effectively reducing the side reactions at the interface between the positive electrode and the electrolyte (or electrolyte) of the lithium-ion battery, and solving the problem of rapid capacity decay of the lithium-ion battery caused by structural changes and / or side reactions during the cycle. In this way, the capacity retention rate of the battery is improved, making it have excellent cycle stability.

[0056] In one embodiment, the solid electrolyte comprises Li 1+x Al x M 2-x (PO4)3, LiTiPO5. M includes at least one of Ti, Ge, Sr, 0.2≤x≤0.5. For example, the solid electrolyte is Li 1.3 Al 0.3 Ti 1.7 (PO3)4、Li 1.4 Al 0.4 Ti 1.6 At least one of (PO3)4 and LiTiPO5.

[0057] In one embodiment, the lithium cobalt oxide includes at least one of high-rate lithium cobalt oxide, high-density lithium cobalt oxide, and high-voltage lithium cobalt oxide.

[0058] In a third aspect of the embodiments of the present application, a lithium-ion battery is provided, comprising a positive electrode, a negative electrode, an electrolyte, a PP separator, a housing, etc. The positive electrode of the lithium-ion battery comprises the composite positive electrode material in the above embodiments.

[0059] In one embodiment, a method for preparing a lithium ion battery comprises the steps of:

[0060] The composite positive electrode material in the embodiment of the present application is used as the active material, the conductive carbon black is used as the conductive agent, and the polyvinylidene fluoride is used as the binder. The above three materials are mixed and dissolved in N-methylpyrrolidone, mixed evenly, coated on aluminum foil, dried, and punched into a positive electrode sheet;

[0061] Provide negative electrode shell, gasket, electrolyte, PP diaphragm, negative electrode plate, positive electrode shell and spring;

[0062] In an argon glove box, a lithium battery was assembled in the order of a negative electrode shell, a gasket, a positive electrode sheet, an electrolyte, a PP diaphragm, an electrolyte, a negative electrode sheet, a gasket, a spring and a positive electrode shell.

[0063] Wherein, the negative electrode plate is a lithium plate, and the electrolyte includes at least one of ethylene carbonate and diethyl carbonate.

[0064] The following is further described through a number of specific embodiments.

[0065] Example 1

[0066] Preparation of composite positive electrode material: According to the mass ratio of solid electrolyte to lithium cobalt oxide of 1wt%:1, 0.1gLi 1.4 Al 0.4 Ti 1.6 (PO3)4 was put into a mortar, and then 10g of ethanol was added and ground until the mortar was completely dry. Then 10g of lithium cobalt oxide was added, and then 10g of ethanol was added and ground until the mortar was completely dry. This process was repeated three times. Then sintering was performed. During the sintering process, the temperature was raised to 900℃ at a heating rate of 5℃ / min and kept at this temperature for 6h. Finally, it was cooled to room temperature to obtain a composite positive electrode material of lithium cobalt oxide coated with a solid electrolyte.

[0067] Preparation of lithium-ion battery: The prepared composite positive electrode material is used as the active material, and PVDF and super-P are dissolved in N-methylpyrrolidone at a mass ratio of 8:1:1. The film is drawn on the aluminum foil of the coating machine, dried, and punched into the positive electrode sheet. Provide the negative electrode shell, gasket, electrolyte (ethylene carbonate and diethyl carbonate), PP diaphragm, negative electrode sheet (lithium sheet), positive electrode shell and shrapnel; assemble the lithium battery in the order of negative electrode shell, gasket, positive electrode sheet, electrolyte, PP diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel and positive electrode shell in an argon glove box. And test it at a cut-off voltage of 4.2V. The results are as follows: Figure 1 shown.

[0068] from Figure 1 It can be seen that the prepared battery still has a capacity retention rate of 101.34% after 500 cycles, indicating that the capacity of the lithium-ion battery in Example 1 does not decay during the long cycle process, and further indicating that the composite positive electrode material in Example 1 can significantly inhibit the interfacial side reactions during the long cycle of the battery, improve the cycle stability of the battery, and thus improve the service life of the battery.

[0069] Example 2

[0070] Preparation of composite cathode material: According to the mass ratio of solid electrolyte to lithium cobalt oxide 2wt%:1, 0.2gLi 1.4 Al 0.4 Ti 1.6(PO3)4 was put into a mortar, and then 10g of ethanol was added and ground until the mortar was dry. Then 10g of lithium cobalt oxide was added, and then 10g of ethanol was added and ground until the mortar was dry. This process was repeated three times. Then sintering was performed. During the sintering process, the temperature was increased to 900℃ at a heating rate of 5℃ / min and kept at this temperature for 6h. Finally, it was cooled to room temperature to obtain a composite positive electrode material of lithium cobalt oxide coated with a solid electrolyte.

[0071] Preparation of lithium-ion battery: The prepared composite positive electrode material is used as the active material, and PVDF and super-P are dissolved in N-methylpyrrolidone at a mass ratio of 8:1:1. The film is drawn on the aluminum foil of the coating machine, dried, and punched into the positive electrode sheet. Provide the negative electrode shell, gasket, electrolyte (ethylene carbonate and diethyl carbonate), PP diaphragm, negative electrode sheet (lithium sheet), positive electrode shell and shrapnel; assemble the lithium battery in the order of negative electrode shell, gasket, positive electrode sheet, electrolyte, PP diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel and positive electrode shell in an argon glove box. And test it at a cut-off voltage of 4.2V. The results are as follows: Figure 2 shown.

[0072] from Figure 2 It can be seen that the prepared battery still has a capacity retention rate of 99.57% after 500 cycles, indicating that the capacity of the lithium-ion battery in Example 2 hardly decays during the long cycle process, and further indicating that the composite positive electrode material in Example 2 can significantly inhibit the interfacial side reactions during the long cycle process of the battery, thereby improving the cycle stability of the battery and thus improving the service life of the battery.

[0073] Example 3

[0074] Preparation of composite cathode material: According to the mass ratio of solid electrolyte to lithium cobalt oxide 3wt%:1, 0.3gLi 1.4 Al 0.4 Ti 1.6 (PO3)4 was put into a mortar, and then 10g of ethanol was added and ground until the mortar was dry. Then 10g of lithium cobalt oxide was added, and then 10g of ethanol was added and ground until the mortar was dry. This process was repeated three times. Then sintering was performed. During the sintering process, the temperature was raised to 900℃ at a heating rate of 5℃ / min and kept at this temperature for 6h. Finally, it was cooled to room temperature to obtain a composite positive electrode material of lithium cobalt oxide coated with a solid electrolyte.

[0075] Preparation of lithium-ion battery: The prepared composite positive electrode material is used as the active material, and PVDF and super-P are dissolved in N-methylpyrrolidone at a mass ratio of 8:1:1. The film is drawn on the aluminum foil of the coating machine, dried, and punched into the positive electrode sheet. Provide the negative electrode shell, gasket, electrolyte (ethylene carbonate and diethyl carbonate), PP diaphragm, negative electrode sheet (lithium sheet), positive electrode shell and shrapnel; assemble the lithium battery in the order of negative electrode shell, gasket, positive electrode sheet, electrolyte, PP diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel and positive electrode shell in an argon glove box. And test it at a cut-off voltage of 4.2V. The results are as follows: Figure 3 shown.

[0076] from Figure 3 It can be seen that the prepared lithium-ion battery still has a capacity retention rate of 97.96% after 500 cycles, indicating that the capacity attenuation of the lithium-ion battery in Example 3 during the long cycle process is extremely low, and further indicating that the composite positive electrode material in Example 3 can significantly inhibit the interfacial side reactions during the long cycle of the battery, improve the cycle stability of the battery, and thus improve the service life of the battery.

[0077] Example 4

[0078] Preparation of composite positive electrode material: According to the mass ratio of solid electrolyte to lithium cobalt oxide of 0.5wt%:1, 0.05gLi 1.4 Al 0.4 Ti 1.6 (PO3)4 was put into a mortar, and then 10g of ethanol was added and ground until the mortar was dry. Then 10g of lithium cobalt oxide was added, and then 20g of ethanol was added and ground until the mortar was dry. This process was repeated three times. Then sintering was performed. During the sintering process, the temperature was increased to 750℃ at a heating rate of 3℃ / min and kept at this temperature for 4h. Finally, it was cooled to room temperature to obtain a composite positive electrode material of lithium cobalt oxide coated with a solid electrolyte.

[0079] Preparation of lithium-ion battery: The prepared composite positive electrode material is used as the active material, dissolved in N-methylpyrrolidone with PVDF and super-P at a mass ratio of 8:1:1, and drawn on the aluminum foil of the coating machine, dried, and punched into a positive electrode sheet. Provide negative electrode shell, gasket, electrolyte (ethylene carbonate and diethyl carbonate), PP diaphragm, negative electrode sheet (lithium sheet), positive electrode shell and shrapnel; assemble the lithium battery in the order of negative electrode shell, gasket, positive electrode sheet, electrolyte, PP diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel and positive electrode shell in an argon glove box.

[0080] Example 5

[0081] Preparation of composite cathode material: According to the mass ratio of solid electrolyte to lithium cobalt oxide 4wt%:1, 4gLi 1.4 Al 0.4 Ti 1.6(PO3)4 was put into a mortar, and then 10g of ethanol was added and ground until the mortar was dry. Then 10g of lithium cobalt oxide was added, and then 10g of ethanol was added and ground until the mortar was dry. This process was repeated three times. Then sintering was performed. During the sintering process, the temperature was raised to 900℃ at a heating rate of 5℃ / min and kept at this temperature for 6h. Finally, it was cooled to room temperature to obtain a composite positive electrode material of lithium cobalt oxide coated with a solid electrolyte.

[0082] Preparation of lithium-ion battery: The prepared composite positive electrode material is used as the active material, dissolved in N-methylpyrrolidone with PVDF and super-P at a mass ratio of 8:1:1, and drawn on the aluminum foil of the coating machine, dried, and punched into a positive electrode sheet. Provide negative electrode shell, gasket, electrolyte (ethylene carbonate and diethyl carbonate), PP diaphragm, negative electrode sheet (lithium sheet), positive electrode shell and shrapnel; assemble the lithium battery in the order of negative electrode shell, gasket, positive electrode sheet, electrolyte, PP diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel and positive electrode shell in an argon glove box.

[0083] Comparative Example 1

[0084] Preparation of positive electrode material: 10g of lithium cobalt oxide was added with 10g of ethanol and ground until dry in a mortar, and this process was repeated three times. Then sintering was performed, and the temperature was increased to 900°C at a heating rate of 5°C / min and kept at this temperature for 6h to obtain lithium cobalt oxide material.

[0085] Preparation of lithium-ion battery: The prepared lithium cobalt oxide material is used as the active material, and is dissolved in N-methylpyrrolidone with PVDF and super-P at a mass ratio of 8:1:1. The film is drawn on the aluminum foil of the coating machine, dried, and punched into the positive electrode. Provide the negative electrode shell, gasket, electrolyte (ethylene carbonate and diethyl carbonate), PP diaphragm, negative electrode sheet (lithium sheet), positive electrode shell and shrapnel; assemble the lithium battery in the argon glove box in the order of negative electrode shell, gasket, positive electrode sheet, electrolyte, PP diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel and positive electrode shell. And test it at a cut-off voltage of 4.2V. The results are as follows: Figure 4 shown.

[0086] from Figure 4 It can be seen that the battery using uncoated lithium cobalt oxide positive electrode material has only 86.69% capacity retention rate after 500 cycles, and the capacity decreases significantly.

[0087] Combining the test results of Examples 1 to 3 and Comparative Example 1, it can be seen that for the composite positive electrode material prepared by the preparation method provided in the embodiments of the present application, the solid electrolyte can completely cover the lithium cobalt oxide. When the composite positive electrode material is used to prepare a battery, the solid electrolyte can block the lithium cobalt oxide in the composite positive electrode material from contacting the electrolyte (or electrolyte) of the battery, effectively reducing the side reactions at the interface between the lithium cobalt oxide in the composite positive electrode material and the electrolyte (or electrolyte), thereby solving the problem of rapid capacity decay of lithium-ion batteries caused by structural changes and / or side reactions during the cycle.

[0088] In summary, the present application prepares a composite positive electrode material by combining mechanical dispersion with one-step sintering, and the preparation method is simple and easily applicable to industrial production. The composite positive electrode material prepared by the preparation method of the present application, when used in lithium-ion batteries, can solve the problem of rapid capacity decay of lithium-ion batteries caused by structural changes and / or side reactions during the cycle. As a result, the battery capacity retention rate does not decay at all or decays less, and has extremely excellent cycle stability.

[0089] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.

Claims

1. A method for preparing a composite positive electrode material, characterized in that: Includes steps: S1. Provide solid electrolyte, lithium cobalt oxide and solvent; S2, mixing the solid electrolyte and the solvent and grinding until the solvent is volatilized to obtain a mixture, wherein the mass ratio of the solvent to the solid electrolyte is 0.005 to 0.08:1; S3, adding the lithium cobalt oxide to the mixture, dropping the solvent into the mixture and the lithium cobalt oxide, and grinding while dropping until the solvent evaporates to obtain a composite positive electrode material precursor, wherein the mass ratio of the solvent to the lithium cobalt oxide is 1 to 2:1; S4, repeating S2 and S3 3-5 times, sintering the composite positive electrode material precursor to obtain a composite positive electrode material, the sintering temperature is 900° C., the sintering heating rate is 5° C. / min, and the sintering time is 6 hours; Wherein, the solvent is anhydrous ethanol, and the mass ratio of the solid electrolyte to the lithium cobalt oxide is 0.005 to 0.01:1, but not 0.01:1; The solid electrolyte is Li 1.4 Al 0.4 M 1.6 (PO3)4; The composite positive electrode material comprises a core layer and a shell layer, wherein the shell layer completely covers the core layer, the material of the core layer is the lithium cobalt oxide, and the material of the shell layer is the solid electrolyte.

2. A composite positive electrode material prepared by the method for preparing a composite positive electrode material according to claim 1.

3. A lithium ion battery, comprising a positive electrode, characterized in that: The positive electrode comprises the composite positive electrode material according to claim 2.

Citation Information

Patent Citations

  • Positive electrode composite material of lithium ion battery and all-solid-state battery containing the same

    CN109449414A

  • Lithium battery positive electrode material and preparation method thereof

    CN111864189A

  • Electrochemical device and inorganic fibres for use therein

    GB201801684D0